(untitled) (Proceedings of the International Conference on Future of Education, 2021)
The abstract should provide a comprehensive summary of the work performed, including the motivation of the research, aim of the research, methods of the research, main results of the research, contribution to the theory and practice of the research. For nine years, the Pushkin State Russian Language Institute has been successfully using the educational and teaching technology - intercultural educational project (IEP) - in teaching Russian as a foreign language. The goal of the project is to ensure intercultural communication among all the participants: foreign students and Moscow schoolchildren. During this project, the audience gets acquainted with the differences between languages and cultures. The specifics of this format of educational and design activities is determined by the relevant factors: the collaboration of foreign students studying Russian, and the other -, native speakers of the Russian language and culture. For the Moscow schoolchildren, the project is a part of their training activities, for the students – an extracurricular educational event. Also, the project concept assumes that both students and children can also become more familiar with (for example, Finland and Vietnam, etc.) each other’s cultures. During the implementation of this technology, representatives of 34 countries took part in it, as well as more than 5,000 Moscow schoolchildren and teachers. The components of reflection are the ability to comprehend the mechanisms that contribute to obtaining certain results; ability to analyze personal cognitive opportunities. Reflection in the educational process implies a thoughtful or sensually experienced process of awareness by the subject of his academic activities. The article aims to present the reflection component of IEP that the authors of the article draw special attention. Participation in the preparation and implementation of activities that demonstrate the results of students’ reflection, reflects the availability of intercultural communication at different levels of language proficiency, enables participants to feel confident in their abilities, motivate them, and increase the effectiveness of language learning. Authors hope that theoretical and practical aspects will contribute to the methods of teaching any foreign language.